Genetic variants associated with steatohepatitis and liver fibrosis in HIV-infected patients with NAFLD - Busca, C.; Arias, P.; Sánchez-Conde, M.; Rico, M.; Montejano, R.; Martín-Carbonero, L.; Valencia, E.; Moreno, V.; Bernardino, J. I.; Olveira, A.; Abadía, M.; González-García, J.; et al. (Frontiers in Pharmacology, 2022)
Background and Aims: Metabolic dysfunction–associated fatty liver disease (MAFLD) is a common cause of liver damage in people living with HIV (PLWHIV). Several studies have investigated candidate genes for susceptibility to MAFLD and to steatohepatitis. PNPLA3, TM6SF2 and MBOAT7-TMC4have been reported to be associated with elevated ALT levels and the histologic parameters of nonalcoholic steatohepatitis and severity of fibrosis. Our objective was to analyze the relationship between PNPLA3, TM6F2, and MBOAT7-TMC4 and steatosis, steatohepatitis, and liver fibrosis in PLWHIV with MAFLD. Method: A cohort of PLWHIV with persistently elevated aminotransferase levels and suspected MAFLD who underwent liver biopsy and determination of genetic variants was assessed at two large centres in Spain. All participants included in the current study were genotyped for rs738409 (PNPLA3), rs58542926 (TM6SF2), and rs641738 (MBOAT7-TMC4). Genomic DNA was extracted from peripheral blood cells using the Chemagen chemagic kit (Perkin Elmer, USA) following the manufacturer’s instructions. SNPs in PNPLA3, TM6SF2, and MBOAT7-TMC4 were analyzed using Sanger sequencing. Results: The study population comprised PLWHIV who were on stable antiretroviral therapy (7.7% women; median age, 49.3 years [44–53.4]). The median CD4 count was 829 (650–980), sixty percent had metabolic syndrome, and 18.5% were diabetic. The median BMI was 28.9 (25.5–30.8). Patients with liver steatosis (any grade) vs nonsteatosis tended to harbor the PNPLA3 G allele variant (57.6% vs 16.7% [p<0.09]), but not TM6SF2 or MBOAT7-TMC4 variants. However, those with steatohepatitis significantly more frequently had the PNPLA3 G allele variant (69.4% vs 39.1% [p<0.05]) and the MBOAT7-TMC4 A allele variant (75% vs 42% [p<0.05]). In our cohort, the TM6SF2 gene variant was not associated with steatosis or steatohepatitis. The PNPLA3 G allele variant was associated with steatohepatitis (OR 4.9 [1.3-18]; p 0.02) and liver fibrosis (OR 4.3 [1.1–17.4]; p 0.04), and the MBOAT7-TMC4 A allele variant was associated with steatohepatitis (OR 6.6 [1.6–27.6]; p 0.01). Conclusions: The PNPLA3 G allele variant and MBOAT7-TMC4 A allele variant were associated with steatohepatitis and liver fibrosis in PLWHIV with persistently elevated aminotransferases and MAFLD. We recommend routine genotyping for PNPLA3 and MBOAT7-TMC4 in PLWHIV with MAFLD to identify those at higher risk of progression.